2024
DOI: 10.1038/s41598-024-51353-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep quality with duty hours, mental health, and medical errors among Japanese postgraduate residents: a cross-sectional study

Kazuya Nagasaki,
Hiroyuki Kobayashi,
Yuji Nishizaki
et al.

Abstract: Long duty hours (DH) impair sleep and negatively affect residents’ health and medical safety. This cross-sectional study investigated the association among residents’ DH, sleep duration, insomnia, sleep impairment, depressive symptoms, and self-reported medical errors among 5579 residents in Japan who completed the General Medicine In-Training Examination (2021) and participated in the training-environment survey. Weekly DH was classified under seven categories. Sleep duration and insomnia symptoms, from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Despite previous studies suggesting optimal overtime duty hours as 80–100 per month (C5) for resident physicians, 3,4,5 our survey revealed that residency program directors now lean towards a much lower limit of 40 hours per month (C3), highlighting a significant evidence-practice gap. This conservative shift, likely influenced by the impending reforms and anticipation of stricter overtime enforcement, suggests a preemptive adjustment for compliance, and also raises concerns regarding the quality of clinical training.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Despite previous studies suggesting optimal overtime duty hours as 80–100 per month (C5) for resident physicians, 3,4,5 our survey revealed that residency program directors now lean towards a much lower limit of 40 hours per month (C3), highlighting a significant evidence-practice gap. This conservative shift, likely influenced by the impending reforms and anticipation of stricter overtime enforcement, suggests a preemptive adjustment for compliance, and also raises concerns regarding the quality of clinical training.…”
Section: Discussioncontrasting
confidence: 90%
“…Approximately half of all resident physicians took the GM-ITE in Japan. 5,6 The survey was conducted from October 18 to December 15, 2023, and included items like the level planned at their own facility, items that fall under working hours rather than self-improvement, and the residency program directors’ perceptions on the optimal working hours for resident physicians. Overtime duty hours per month was divided into eight categories (C1 to C8) (Supplementary file 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that sleep quality has a significant impact on health ( 15 , 16 ), especially among HCWs ( 17 , 18 ). Poorer sleep quality may lead to lower work productivity ( 19 ), more medical errors ( 20 ) and burnout ( 21 ) for HCWs. Research has identified that both personal (such as education and socio-economic status) ( 22 , 23 ) and work-related factors (like job type and workload) ( 24 ) influence HCWs’ sleep quality.…”
Section: Introductionmentioning
confidence: 99%